Efektivitas Program “CERDIK” dalam Meningkatkan Pengetahuan dan Sikap Pencegahan Diabetes Mellitus tipe 2 pada Siswa SMP Ma’had Islam Semarang - Meylina Novita Sari; Fidya Nur Fajrina; Gitta Dhiana Saputri; Niken Mashitoh; Adinda Wisha Maharani; Aura Delillah; Najwa Aulia Rahma Larsana Putri (Journal of Health, Medical, and Psychological Studies, 2026)
Adolescent lifestyle changes characterized by excessive consumption of sugary foods and beverages combined with low physical activity have increased the risk of Type 2 Diabetes Mellitus at a younger age. This study aimed to analyze the effectiveness of the CERDIK Program (Cegah Risiko Diabetes dengan Kendalikan Gula) in improving knowledge and preventive attitudes toward Type 2 Diabetes Mellitus among students of SMP Ma’had Islam Semarang. The study employed a quantitative quasi-experimental design using a one-group pre-test–post-test approach involving 30 students selected through total sampling. Data were collected using structured questionnaires and analyzed using the Wilcoxon Signed Rank Test with a significance level of 95% (α=0.05). The results demonstrated significant improvements in both knowledge and preventive attitudes after the intervention. The median knowledge score increased from 70 to 90, while the median attitude score improved from 75 to 83.75, with p-value <0.001. The CERDIK Program proved effective in promoting preventive behavior and strengthening adolescent health literacy regarding Type 2 Diabetes Mellitus prevention in school settings.